Second International Conference on Crimean-Congo Hemorrhagic Fever - Spengler, Jessica R.; Bente, Dennis A.; Bray, Mike; Burt, Felicity; Hewson, Roger; Korukluoglu, Gülay; Mirazimi, Ali; Weber, Friedemann; Papa, Anna (Antiviral research, 2018)
The Second International Conference on Crimean-Congo Hemorrhagic Fever (CCHF) was held in Thessaloniki, Greece, from September 10–13, 2017, and brought together international public health professionals, clinicians, ecologists, and basic laboratory researchers. Nearly 100 participants, representing 24 countries and the World Health Organization (WHO), were in attendance. Meeting sessions covered the epidemiology of CCHF in humans; ticks and virus-tick interactions; wild and domestic animal hosts; molecular virology; taxonomic classification; pathogenesis and animal models; clinical aspects and diagnosis; clinical management and clinical trials; and disease prevention in humans. The concluding session focused on recent WHO recommendations for public health measures and future research. This report summarizes lectures by the invited speakers and highlights advances in the field. •Crimean-Congo hemorrhagic fever (CCHF) is a tick-borne zoonotic disease seen exclusively in humans.•The Second International CCHF meeting was held in Thessaloniki, Greece, in September 2017.•Nearly 100 participants, representing 24 countries and the World Health Organization (WHO), were in attendance.•Speakers from the WHO supported increased interest in CCHF, presenting several CCHF-focused initiatives.•An International Society on CCHF was proposed, approved, and formed at the meeting.